2020
DOI: 10.1177/1534734620904819
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Prognosis of Diabetic Foot Ulcers: Predictive Value of Neutrophil-to-Lymphocyte Ratio and Red Blood Cell Distribution Width

Abstract: The aim of this study was to investigate the prognostic values of neutrophil-to-lymphocyte ratio and red blood cell distribution width in diabetic foot ulcers treatment. A total of 250 adult patients who were treated in our clinic between 2007 and 2018 for diabetic foot ulcers were evaluated retrospectively. Diabetic foot ulcers were divided into 4 groups: major amputation, minor amputation, chronic wound, and complete healing. The mean age of our study groups was 60 years (range = 55-65 years). The mean follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Only few studies have focused so far on the RDW in patients with DFUs. A previous study with a small sample size in Turkey reported that RDW was a predictive parameter for major amputation in patients with DFUs [ 26 ]. A recent conference abstract with little available detail indicated that RDW was a risk factor for all-cause mortality in a moderate-sized cohort of patients undergoing amputations due to DFUs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies have focused so far on the RDW in patients with DFUs. A previous study with a small sample size in Turkey reported that RDW was a predictive parameter for major amputation in patients with DFUs [ 26 ]. A recent conference abstract with little available detail indicated that RDW was a risk factor for all-cause mortality in a moderate-sized cohort of patients undergoing amputations due to DFUs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils have been proven to play a critical role in DFU (14-17). Arican et al showed that the neutrophil-tolymphocyte ratio can be a predict the prognosis of DFU, and a high neutrophil-to-lymphocyte ratio inhibits the healing process (15). Yang et al also found that citH3, a neutrophil extracellular trap (NET) specific marker, acts as an inhibitor in wound healing (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a total of 22 studies involving 8832 patients were considered for review. 28-49 Between-study differences in design, methods, clinical characteristics, parameters evaluated, and data reporting did not allow a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Two further studies investigated the role of NLR in predicting the risk of amputation in patients with DM foot ulcers. 30,31 The first was a retrospective study including 101 patients in which NLR values on admission and at day 14 of treatment were matched with laboratory and clinical data. 30 Baseline NLR was higher in severe cases classified in accordance with both Wagner and PEDIS infection scores (Wagner score: NLR 6.7 vs 4.2; P = .04; PEDIS score: NLR 6.3 vs 3.6; P = .03).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation